The relative effectiveness of web advertisement (tested in the Malaysian context) - Liw, Ivy Cheh Chean (2000)
Internet advertising is rapidly emerging as a key strategic tool for generating traffic and stimulating trial at consumer-oriented WebSites. The unpredictability and the lack of measurability and target ability and the creative limitations of Internet advertising cause advertisers to face considerable uncertainty in the "online environment". The purpose of this study is to provide a clearer understanding of the "banner ads" effectiveness normally found in the website. This study is to replicate and extend previous studies of Stevenson (2000) and Rae, Nathan & Brennan, Mike (1998) by further exploring the advertising Hierarchy-of-Effects and its antecedents in the context of web advertising. In doing this, the effects of webpage complexity and dynamic content on the banner ads' effectiveness were examined in Malaysian context. Findings suggest that ad with both moderate graphical and textual animation has positive effects on ad's effectiveness (A WebSite, A Brand, and A Attention/Recall), whereas background complexity has negative effects. A WebSite should be considered as antecedents to the flow of advertising Hierarchy-of-Effects. This shows that the Hierarchy-of-Effects model proposed by Lavidge and Steiner (1961) observed in the traditional media can be applied in the web environment. Future research into the relative effectiveness of factors other than A Ad, A Brand and CI in web advertising and A WebSite is required. In addition, the sequences of effects between variables of A WebSite, A Ad, A Brand, A Atttention/Recall and CI should be investigated and the flow of "Web Hierarchy-of-Effects model" examined. The present study was limited to the respondents who have knowledge in web advertising. Thus, further research into the relative effectiveness on web Hierarchy-of-Effects of person who has experience versus person without experience is needed.